CLEAR - Contact lens complications. Issue 2 (April 2021) - Stapleton, Fiona; Bakkar, May; Carnt, Nicole; Chalmers, Robin; Vijay, Ajay Kumar; Marasini, Sanjay; Ng, Alison; Tan, Jacqueline; Wagner, Heidi; Woods, Craig; Wolffsohn, James S.
Abstract: Contact lens-related complications are common, affecting around one third of wearers, although most are mild and easily managed. Contact lenses have well-defined anatomical and physiological effects on the ocular surface and can result in other consequences due to the presence of a biologically active material. A contact lens interacts with the tear film, ocular surface, skin, endogenous and environmental microorganisms, components of care solutions and other antigens which may result in disease specific to contact lens wear, such as metabolic or hypersensitivity disorders. Contact lens wear may also modify the epidemiology or pathophysiology of recognised conditions, such as papillary conjunctivitis or microbial keratitis. Wearers may also present with intercurrent disease, meaning concomitant or pre-existing conditions unrelated to contact lens wear, such as allergic eye disease or blepharitis, which may complicate the diagnosis and management of contact lens-related disease. Complications can be grouped into corneal infection (microbial keratitis), corneal inflammation (sterile keratitis), metabolic conditions (epithelial: microcysts, vacuoles, bullae, tight lens syndrome, epithelial oedema; stromal: superficial and deep neovascularisation, stromal oedema [striae/folds], endothelial: blebs, polymegethism/ pleomorphism), mechanical (corneal abrasion, corneal erosion, lens binding, warpage/refractive error changes; superior epithelial arcuate lesion, mucin balls, conjunctival epithelial flaps, ptosis, discomfort), toxic and allergic disorders (papillary conjunctivitis, solution-induced corneal staining, incomplete neutralisation of peroxide, Limbal Stem Cell Deficiency), tear resurfacing disorders/dry eye (contact lens-induced dry eye, Meibomian gland dysfunction, lid wiper epitheliopathy, lid parallel conjunctival folds, inferior closure stain, 3 and 9 o'clock stain, dellen, dimple veil) or contact lens discomfort. This report summarises the best available evidence for the classification, epidemiology, pathophysiology, management and prevention of contact lens-related complications in addition to presenting strategies for optimising contact lens wear.